Investigations on macro-drilling by indigenously developed ECM apparatus - Pathak, Sunil; Siti Nadiah, Mohd Saffe; Khilji, Irshad Ahamad (Centre for Advanced Research on Energy (CARe), 2019)
New materials such as hastalloy, nitralloy, nimonicies, carbides etc., are difficult to be machined and find applications in aircrafts, nuclear reactors, turbines, Special cutting tools etc. Although most of the new machining processes have been developed specifically for newer materials that are difficult to be machined, some of these processes were used in the production of complex shapes and cavities. The present work is focused on development of Electrochemical Machining (ECM) and its testing for macro-drilling application. The apparatus has been indigenously developed and study of few of the most important parameters of ECM has been done on material removal rate.